Correlations between Age and Hypertension on Diabetic Foot Ulcer - Vitania Marsya; Iin Novita Nurhidayati Mahmuda; Nining Lestari; Safari Wahyu Jatmiko (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: Diabetic foot ulcer is a wound located on the foot of a diabetic patient, which is related to peripheral neuropathy or arterial disease. Hypertension can be related to diabetic foot ulcer by its mechanism that caused peripheral artery disease. Age also can be the one of risk factors for diabetic foot ulcers, because aging occurs a reduction of insulin secretion, even insulin resistance. Insulin resistance occurs in macroangiopathy. The purpose of this study is to determine the correlation between age and hypertension with diabetic foot ulcers.Subjects and Method: This was a cross-sectional study conducted at Arafah Islamic Hospital Rembang, Central Java. The dependent variable is diabetic ulcers. The independent variables were age and hypertension. A sample of diabetic patients using medical records from January 2022-June 2022. Data were collected using purposive sampling and analyzed using the Chi-Square test, and regression logistic test.Results: Significant correlation was found between age (OR= 3.80; 95% CI= 1.38 to 10.57; p<0.001) and hypertension (OR= 8.12; 95% CI= 2.70 to 24.40; p<0.001) with a diabetic foot ulcer.Conclusion: There is a significant correlation between age and hypertension with diabetic foot ulcers.Keywords: age, hypertension, diabetes, diabetic foot ulcers.Correspondence: Nining Lestari. Bachelor of Medicine, Muhammadiyah University of Surakarta. Jl. A. Yani, Mendungan, Pabelan, Kartasura, Sukoharjo 57162, Central Jawa, Indonesia. Email: nl209@ums.ac.id. Mobile: +62852-2939-0353Indonesian Journal of Medicine (2023), 08(02): 179-185https://doi.org/10.26911/theijmed.2023.08.02.07